Expressive and Representative Utterances in Hotel Transylvania Movie Script - Abigael Adeliana Langi Karaeng (ELITE: Journal of English Language and Literature, 2016)
This research is intended to describe the use of expressive and representative utterances Hotel Transylvania movie script. The research question of this research is, namely: how expressive and representative utterances are used in the Hotel Transylvania movie script. The research methodology used in this research is the descriptive qualitative method. The source of data in this research is Hotel Transylvania movie script and Hotel Transylvania movie. To collect the data the researcher used some steps: downloading the movie script and the movie, reading and watching repeatedly and comprehensively the movie and script, and identifying conversations that contain expressive and representative utterances found in Hotel Transylvania. The results of this research are described as follows: The researcher divided the data into two, the first is data expressive utterances and the second data is representative utterances. The researcher found 32 data of expressive utterances, they were welcome/greeting (9 data), thanking (7 data), condoling (3 data), deplore (5 data), and apologizing (8 data) and there are 20 data of representative utterances which included reporting (4 data), complaining (4 data), stating (5 data), concluding (3 data), and suggesting (4 data). The expressive utterance has more data because most of the characters express how they met and parted with someone at the hotel, thanking, saying sorry, expressing sympathy, expressing dislike, and congratulating.   Keywords: Speech Act, Illocutionary Act, Expressive, Representative